Analysis of character education content in 2013 social studies curriculum text books - Rahmasari, Kurnia; Sapriya, Sapriya; Kurniawati, Yeni (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
Character education is the basis for forming a nation's quality character that does not ignore social values. This study aimed to determine the content of character education in the 2013 Curriculum Social Studies textbook. The method in this research is narrative content analysis with a qualitative approach. The data collection techniques used were documentation studies, text analysis of the social studies lesson in the 2013 curriculum for class VIII, and an interview with one of the social studies teachers who used this textbook. The research results obtained include: (1) The content of character education in the revised edition of the 2017 social studies subject textbook has been adjusted to the Regulation of the Minister of Education and Culture Number 20 of 2018 concerning Strengthening Character Education (PPK); (2) In the revised edition of the 2017 Social Studies textbook issued by the Ministry of Education and Culture, there are eight values in character education, namely religious, honest, disciplined, responsible, mutual cooperation, polite, tolerance, and trust self; and (3) Based on the results of the character load table that has been explained, it can be seen that there are 18 sentences that imply indicators of several character values and six sentences that explicitly contain several character values.